2017
DOI: 10.3390/rs9101045
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Variation of Snow Cover in Tianshan Mountains, Central Asia, Based on Cloud-Free MODIS Fractional Snow Cover Product, 2001–2015

Abstract: Abstract:The change in snow cover under climate change is poorly understood in Tianshan Mountains. Here, we investigate the spatiotemporal characteristics and trends of snow-covered area (SCA) and snow-covered days (SCD) in the Tianshan Mountains by using the cloud-removed MODIS fractional snow cover datasets from 2001-2015. The possible linkage between the snow cover and temperature and precipitation changes over the Tianshan Mountains is also investigated. The results are as follows: (1) The distribution of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
48
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 82 publications
(49 citation statements)
references
References 46 publications
1
48
0
Order By: Relevance
“…They found statistically significant negative trends in snow cover duration, date of snow cover onset, and date of snowmelt across most of the basin, except trends of earlier snow onset in the Central Pamir, especially at elevations greater than 4000 m . Tang et al (2017) found that maps of snow cover days based on cloud-screened MODIS daily snow products exhibited a high mean (> 85%) consistency with in-situ observations of snow cover days. Their analysis focused on the Tien Shan range divided into four regions of which Central Tien Shan corresponds most closely to our study area.…”
Section: Discussionmentioning
confidence: 80%
See 4 more Smart Citations
“…They found statistically significant negative trends in snow cover duration, date of snow cover onset, and date of snowmelt across most of the basin, except trends of earlier snow onset in the Central Pamir, especially at elevations greater than 4000 m . Tang et al (2017) found that maps of snow cover days based on cloud-screened MODIS daily snow products exhibited a high mean (> 85%) consistency with in-situ observations of snow cover days. Their analysis focused on the Tien Shan range divided into four regions of which Central Tien Shan corresponds most closely to our study area.…”
Section: Discussionmentioning
confidence: 80%
“…Their analysis focused on the Tien Shan range divided into four regions of which Central Tien Shan corresponds most closely to our study area. Using simple linear regression to identify and characterize trends, Tang et al (2017) found in the mean snow-covered area in each of four seasons in the Central Tien Shan ranging from a minimum of −8% in autumn to maximum of −14% in spring, but no trend was statistically significant at p < 0.05. They also calculated a decrease of −12% in the duration of snow cover in the Central Tien Shan from 2001-2015, but it was also not significant.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations